(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
Life skills education is an education that must be passed by everyone without exception. In order to support the realization of life skills education for all, we try to facilitate youth capacity building through digital marketing training. This program is a limited program because it is intended for young people who graduated from high school but have never interned or worked. To be able to survive in the community again after graduating from high school or termination of employment (layoffs) after the COVID-19 pandemic, at least young people have the life skills to find or open up new livelihoods. Therefore, young people must be equipped with skills that are in line with the needs of the current job market. Digital marketing skills are one of the most popular and needed skills at this time, so this skill was chosen as a life skills education option that can be offered by the implementing team in this year’s service.